The Korean Wave in Latin America as a result of multiculturalism (2020)
The popular South Korean-culture revolution in Latin America was brought about as a social and cultural paradigm supported by the economic success attained by the Asian power. Since the introduction of capitalist Fordism, international context has provided key tools for market distribution and maximization, leading to the emergence of multiculturalism as a new version of capital globalization. This paper examines Hallyu’s consolidation in Latin America, fueled by capitalism and cultural diversity.